Exploration of the Integrated Development Path of Intangible Cultural Heritage and Tourism Industry from the Perspective of Intellectual Property—Take Shaoxing City as An Example - Wang, Hang (Journal of Global Economy, Business and Finance, 2025)
Intangible cultural heritage, as the soul of the nation and the region, not only carries deep historical heritage, but also is a bridge to spread traditional culture and continue the national spirit. In such an era, how to combine the intangible cultural heritage with tourism industry has become an important proposition to enhance the national cultural soft power and promote the protection of intangible heritage. Shaoxing, as one of the first 24 famous historical and cultural cities, has a long history, deep cultural heritage and numerous intangible cultural heritages, and is known as a museum without walls. Taking Shaoxing as an example, the article discusses in depth how to deeply integrate the intangible cultural heritage with the tourism industry through the creation of cultural IPs, providing new ideas for the protective development of intangible heritage.